DC and DP polarographic studies to explore the intermediate species form and operating conditions effects on electrodeposition of Cu from Cu(II) in the presence of alizarin red S - Ali, Nour Mohammad-Sadik; Vemuri, Suresh; Bhagat, Dharini; Karam, Ayman; Pati, Ranjan; Ray, Abhijit; Mukhopadhyay, Indrajit (Chemical papers, 2022)
The reduction of Cu(II) has been investigated in the presence of Alizarin Red S in two different background solutions namely KCl and acetate buffer through this study. The electroactive intermediate species have been extensively characterised by using Direct Current Polarography and Deferential Pulse Polarography techniques. It has been observed that Cu 2+ was reduced to elemental copper in a two-step single-electron transfer process. However, the kinetics of charge transfer is dampened in the presence of Alizarin due to the complexation of active copper ions with ionised Alizarin, making the electrodeposition more controlled. In the first technique, the peaks of the 57 mM-Cu 2+ reduction and for the 57 mM-Alizarin reduction have been observed. Using the second technique, the voltammograms exhibit the peaks at pH = 2, 3, where the first peak is for the reduction process of two carbonyl groups in Alizarin, and the second one is for Cu 2+ reduction as one-step two-electron transfer. At pH = 5, the complex formation reveals that copper can be hardly reduced on the cathode, whereas Alizarin has two small peaks for two carbonyl groups after being in the investigated alkali mediums. The clear peak at pH = 11 indicates that copper is no more in the structure of a complex. The stoichiometries of the salt and complex have been also verified where both are (1:1). Coating experiments were carried out at 25 °C, 35 °C and 60 °C to investigate the relations between the current efficiency and pH, current density, molarity concentration and time and obtain the optimal operating conditions for copper electrodeposition on steel and stainless steel.